Crystallization firing effect on the marginal discrepancy of the IPS. emax CAD crowns using two different CAD/CAM systems - Ghadeer , Fatima K; Alwan , Lateef E; Al-Azzawi, Abdul Kareem J (Journal of Baghdad College of Dentistry, 2023)
Background: Marginal adaptation is critical for long – term success of crown and bridge restoration. Computer aided design / computer aided manufacture (CAD/ CAM) system is gaining more importance in the fabrication of dental restoration. Objective: The aim of this study is to evaluate the effect of crystallization firing on the vertical marginal gap of IPS. emax CAD crowns which fabricated with two different CAD/CAM systems .Materials and Methods: Twenty IPS e.max CAD crowns were fabricated. We had two major groups (A, B) (10 crowns for each group) according to the CAD/CAM system being used: Group A: fabricated with Imes - Icore CAD/CAM system; Group B: fabricated with In Lab Sirona CAD/CAM system. Each group was subdivided into two subgroups pre-crystallized (Group A1, B1) and crystallized crowns (Group A2, B2). At four points on each aspect of the crown, marginal gaps were assessed on the master metal die by using digital microscope at a magnification of (110X) and image- J program. The measurement was done twice for each crown; before and after crystallization process.Results: The lowest mean of marginal gap before and after crystallization was (29.387±2.774μm) and (70.108±5.569μm) respectively for Group A (Imes - Icore system) and the highest mean value before and after crystallization was (51.728 ±3.774μm) and (84.071 ±4.567μm) respectively for Group B (Sirona system). Paired sample t-test result showed a statistically highly significant difference in marginal gap between all groups.Conclusions: The crystallization process increases the vertical marginal gap. Imes - Icore system showed the lower marginal gap than Sirona system. The two systems have an acceptable marginal gap